Molecular epidemiology of Staphylococcus aureus among food handlers and in cooked food in the Klang Valley, Malaysia - Seow, Wen Li (2020)
World Health Organization (WHO) stated that the burden of foodborne disease achieves 600 million cases each year with one of ten people in the world falls ill after consuming contaminated food. In Malaysia along, food poisoning cases were occupied 15,023 cases in 2018. The foodborne illness is associated with poor handling of cooked food by the food handlers rather than cross-contamination from raw food in food premises. This study aimed to (i) determine the prevalence of both S. aureus hand carriers and methicillin resistant S. aureus (MRSA) strains among food handlers and in cooked food, (ii) identify the correlation between the socio-demographic characteristics profile of the food handlers with the prevalence and multidrug resistant (MDR) S. aureus strains among food handlers, and (iii) evaluate the epidemiological relationship among S. aureus strains obtained from food handlers’ hands and cooked food samples. Two hundreds hand swab samples with 100 cooked food samples were collected from Grade A, B, and C food premises throughout Klang Valley which socio-demographic information of food handlers was recorded. Several analyses were performed to detect the presence of S. aureus and MRSA, such as mannitol salt agar test, biochemical tests, and antimicrobial susceptibility test. DNA extraction and polymerase chain reaction (PCR) analysis for phylogenetic sequence analysis were further performed. Statistical analysis was done by using the software IBM SPSS Statistic 22. The results showed that the prevalence of S. aureus among food handlers and cooked food were 95.0% and 50.0%, respectively. None of the food handlers inhered MRSA strains with four (8.0%) cooked food samples were detected with MRSA strains. Further Fisher-Freeman Halton analysis revealed that there was no significant correlation between food handlers’ socio-demographic profile and the prevalence of S. aureus. The occupational information and lifestyle habits of food handlers, however, were correlated to the prevalence of S. aureus. The grading system authorized by local authorities (P = 0.000), grades of food premises (P = 0.010), years of employment (P = 0.049) and working responsibility (P = 0.026) of food handlers were significantly correlated with the prevalence of S. aureus. Nonetheless, no correlation was found between MDR S. aureus with the socio-demography profile, occupational information and lifestyle habits of food handlers. On the other hand, PCR molecular analysis identified that the overall prevalence of S. aureus and MRSA among food handlers was 25.0% and 1.0%, respectively. For cooked food samples, the prevalence of S. aureus was 9.0%. The further phylogenetic tree sequencing analysis showed that most of the cooked food samples had different similarities with the food handlers’ S. aureus strains. However, there was epidemiological relationship between food handler (HL11) and cooked food (F11) which the current study assumed that cross contamination from food handler to food was occurred during food preparation. This urges for the improvements in constructive and sustainable food safety practises among food handlers to reduce the risk of foodborne illness outbreaks.